2022
DOI: 10.1177/15589250221091819
|View full text |Cite
|
Sign up to set email alerts
|

Development of an ergonomic protective suit for physiotherapists during the COVID-19

Abstract: During the COVID-19 pandemic, the provision of appropriate protective clothing for medical staff who must continue to perform their duties at this period is of particular importance. Physiotherapists are not allowed to suspend working during this time either, and the specifics of their work is close contact with the patient within various movements during the therapy process. Inadequate (intended for general use) protective clothing affects work capacity in the aspects of movement restriction, thermal comfort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…It has been shown that the safety properties of protective clothing are mainly focused on the structure and materials of protective clothing [5]. In particular, special attention should be paid to the airtightness of protective clothing in terms of the structure of protective clothing.…”
Section: Safety Principles For Protective Clothing Designmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the safety properties of protective clothing are mainly focused on the structure and materials of protective clothing [5]. In particular, special attention should be paid to the airtightness of protective clothing in terms of the structure of protective clothing.…”
Section: Safety Principles For Protective Clothing Designmentioning
confidence: 99%
“…(3) The material of the existing medical protective clothing is not able to absorb the large amount of sweat produced by the health care workers at work. (4) The cold appearance of existing medical protective clothing can easily give patients negative psychological implications (5). The sizes of the existing protective clothing do not match the size of the health care workers and lack elasticity.…”
mentioning
confidence: 99%
“…Despite there being several studies (e.g. cold protective clothing, 29 motorcycle protective clothing, 30 protective suits for physiotherapists, 31 sports clothing, 32 and ski suits 33 ) on modular clothing based on body mapping of sweating patterns, no research has been conducted on outdoor workwear with optimal fabric selection. The majority of previous studies focused on the uniform requirements of wearers, often using identical fabrics (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of in-service outdoor workwear covered environmental hazards, activity features, and subjective demands, such as protection, comfort, ergonomics, and compatibility. Multi-function partitioned design approaches [29][30][31][32][33] were then combined to develop the overall fabric design for outdoor workwear. Regarding fabric selection, we utilized an integrated ECM-AHP-Entropy-TOPSIS method as an MCDM tool for selecting and ranking suitable fabrics for outdoor workwear.…”
Section: Introductionmentioning
confidence: 99%